The Contribution of Academician Bektemir Murzubraimov to the Development of Chemical Sci- ence in Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the scientific and pedagogical work of academician B. Murzubraimov and his contribution to the development of higher pedagogical education in Kyrgyzstan. Through his scientific and pedagogical work, he exerted a significant influence on the training of teachers for pedagogical education, which was sorely needed by the republic’s pedagogical universities. He analyzed and assessed the development of higher pedagogical education, which requires special consideration.
Keywords: knowledge, education, science, development, training, activity